Pengaruh Literasi Perpajakan, Subjective Norms, Dan Self Efficacy Terhadap Minat Berkarier Sebagai Konsultan Pajak Pada Mahasiswa Akuntansi Generasi Z : Studi Kasus Mahasiswa Akuntansi Di Kota Serang - Isnaeni Yuliawati; Mochamad Fahru Komarudin; Novi Handayani (Jurnal Ekonomi Bisnis dan Akuntansi, 2026)
The demand for tax professionals, particularly tax consultants, continues to increase in Indonesia, while the number of practicing tax consultants remains insufficient to meet this demand. Although Serang City has considerable potential through its accounting students, their interest in pursuing a career as a tax consultant remains relatively low. This study aims to examine the influence of tax literacy, subjective norms, and self efficacy on accounting students' interest in pursuing a career as a tax consultant in Serang City. This study employed a quantitative research method with a survey approach. A total of 94 respondents were selected using the Slovin formula through non-probability sampling with an accidental sampling technique. Data were collected using questionnaires. The results indicate that tax literacy has a negative and significant effect on students' career interest as tax consultants, while subjective norms and self efficacy have positive and significant effects. Furthermore, all three variables simultaneously have a significant effect on career interest as tax consultants. The findings are expected to provide valuable input for universities and professional organizations in developing strategies to increase accounting students' interest in pursuing careers as tax consultants.